PENGARUH GOOD CORPORATE GOVERNANCE, MAQASHID SHARIA, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Bank Umum Syariah di Indonesia Periode 2012-2017) - M. Syaiful Padli; Nur Diana; Afifudin Afifudin (Universitas Islam Malang, 2019)
ABSTRACTThis study aims to determine the effect of Good Corporate Governance,Maqashid Sharia, and Profitability to Economic Value Added at IndonesianIslamic Commercial Banks registered in the Financial Services Authority (OJK)for the 2012-2017 period, with purposive sampling technique for islamiccommercial banks in 2012-2017 and using multiple linear regression analysis.The results showed that the Good Corporate Governance (GCG) has a significantpositive effect on Economic Value Added (EVA). Maqashid Sharia (MSI) has noeffect on Economic Value Added (EVA). Profitability (ROA) has no effect onEconomic Value Added (EVA).Keywords : Good Corporate Governance, Maqashid Sharia, Profitability,Economic Value Added